Antiviral activity of digoxin and ouabain against SARS‐CoV‐2 infection and its implication for COVID‐19 (2020)
The current coronavirus (COVID-19) pandemic is exacerbated by the absence of efective therapeutic agents. Notably, patients with COVID-19 and comorbidities such as hypertension and cardiac diseases have a higher mortality rate.An efcient strategy in response to this issue is repurposing drugs with antiviral activity for therapeutic efect. Digoxin (DIG) and ouabain (OUA) are FDA drugs for heart diseases that have antiviral activity against several coronaviruses. Thus, we aimed to assess antiviral activity of DIG and OUA against SARS-CoV-2 infection.The half-maximal inhibitory concentrations (IC50) of DIG and OUA were determined at a nanomolar concentration. Progeny virus titers of singledose treatment of DIG, OUA and remdesivir were approximately 103 -, 104 - and 103 -fold lower (> 99% inhibition), respectively, than that of non-treated control or chloroquine at 48 h post-infection (hpi). Furthermore, therapeutic treatment with DIG and OUA inhibited over 99% of SARS-CoV-2 replication, leading to viral inhibition at the post entry stage of the viral life cycle. Collectively, these results suggest that DIG and OUA may be an alternative treatment for COVID-19, with potential additional therapeutic efects for patients with cardiovascular disease.